2009
DOI: 10.1055/s-0029-1224156
|View full text |Cite
|
Sign up to set email alerts
|

Improved Endothelial Function and Lipid Profile Compensate for Impaired Hemostatic and Inflammatory Status in Iatrogenic Chronic Subclinical Hyperthyroidism of Thyroid Cancer Patients on L-T4 Therapy

Abstract: Chronic subclinical hyperthyroidism was associated with improved endothelial function and lipid profile, while haemostatic and inflammatory parameters were impaired. The two opposite mechanisms may well compensate for each other at the level of the vessel wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
2
11
0
1
Order By: Relevance
“…Patients with hypothyroidism are known to have significantly higher serum total cholesterol, low-density lipoprotein cholesterol (LDL-C), and triglyceride levels compared to healthy population. In addition, carotid intima-media thickness and flow-mediated vasodilatation, which are surrogated markers of atherosclerosis and vascular endothelial dysfunction, are also known to be associated with thyroid function, even when TSH level is within normal reference range [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Patients with hypothyroidism are known to have significantly higher serum total cholesterol, low-density lipoprotein cholesterol (LDL-C), and triglyceride levels compared to healthy population. In addition, carotid intima-media thickness and flow-mediated vasodilatation, which are surrogated markers of atherosclerosis and vascular endothelial dysfunction, are also known to be associated with thyroid function, even when TSH level is within normal reference range [25]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been also shown that thyroid hormones cause rapid relaxation of vascular smooth muscle (endothelium-independent vasodilatation) [38]. Recently, we found better endothelial function while slightly impaired vascular injury markers and inflammatory status in subclinical hyperthyroidism [39]. We concluded that these apparently opposing mechanisms may compensate for each other at the level of the vessel wall.…”
Section: Discussionmentioning
confidence: 69%
“…[21,22]. One of the recently described tools for determining cardiovascular risk is arterial wall stiffness which is an independent predictor of cardiac events [23] via several mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased cardiac output, stroke volume, end diastolic volume and increased peripheral resistance have been demonstrated in short-term hypothyroidism [4]. Increased cardiovascular risks associated with high serum total cholesterol, low density lipoprotein (LDL) cholesterol and homocysteine levels have been found in previous studies on short-term hypothyroidism [5][6][7]. On the other hand, no significant change has been observed in the concentrations of atherogenic small dense LDL and large very low density lipoprotein (VLDL) in patients with short term hypothyroidism [8].…”
mentioning
confidence: 97%